UMP sends KILAU Volunteers to help flood victims in Baling - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
BALING, 15 July 2022 - It was disheartening for KILAU UMP volunteers team when they arrived at Kampung Masjid Iboi in Baling, which was hit by the tragedy of floods and headwater.